Respuesta :

Answer:

Answer: Is third one

hope it help you

Thank u

Answer:

D. (∜(2x-8)^4=(-∜(2x+8)^4

Step-by-step explanation:

∜(2x-8)+∜(2x+8)=0        

Rearrange the radical on the left side of the equation

∜(2x-8)=-∜(2x+8)

Raise both sides to the 4 power

(∜(2x-8))^4=(-∜(2x+8))^4

Determine the sign for exponential or radical expressions

(∜(2x-8))^4=(∜(2x+8))^4

Simplify the radical expression

2x-8=(∜(2x+8))^4

Simplify the radical expression

2x-8=2x+8

Rearrange variables to the left side of the equation

2x-2x=8+8

Apply the Inverse Property of Addition

0=8+8

Simplify

0=16

No solution

The step that makes the most sense is D. (∜(2x-8)^4=(-∜(2x+8)^4